THU0310 Predictors of Therapeutic Success of Steroids Injection in the Carpal Tunnel Syndrome: A Retrospective Multivariate Analysis of A Multicenter Cohort. (10th June 2014) - Guillen Astete, C.A.; Luque Alarcon, M.; Boteanu, A.; Zea, A.
Abstract : Background: Treatment of moderate to severe carpal tunnel syndrome includes the possibility of local steroid injections, however the treatment success rate and its duration are very variable. There is no study designed to predict if a local steroid injection will be success or not. Sometimes local steroids injections delays surgical procedures without solving patient symtoms. A marker capable to predict success of failure should be useful in terms of chosing best therapy for these patients. Objectives: The purpose of this study was to determine the weight of different factors as predictors of the therapeutic success of steroid joint injections. Methods: We conducted a retrospective study with a cohort of 166 patients diagnosed with moderate or severe carpal tunnel syndrome according to electrophysiological criteria and who had undergone carpal ultrasound between 2010 and 2013. A multivariate analysis, using as the variable response a reduction in the score at the Boston Carpal Tunnel Syndrome Questionnaire three months after the steroid infiltration was performed. Results: The presence of positive power- Doppler signal in the carpal tunnel showed a high correlation with the improvement at the Boston Carpal Tunnel Syndrome Questionnaire (Pearson r -0.7079, p=0.0001) in the bivariate analysis, and a ratio of 49.8% in the multivariate analysis (Heat coeff -0.4777 [95% CI -1.4775 to -0.5612], p<0.0001). Other relevant variables were: duration of symptoms (Heat coeff 0.0071 [95% CI 0.0025 to 0.0117], p=0.0027), the cross-sectional area of the median nerve within the carpal tunnel (Heat coeff 0.0223 [95% CI 0.0023 to 0.0424], p=0.0293) and age (0.0029 Heat coeff [CI -0.0005 to 0.0064], p=0.0979). Conclusions: Our results suggest that the therapeutic success of infiltration is mainly associated with the finding of power- Doppler signal. According to our analysis we believe it is reasonable to recommend steroids joint injections in patients with this finding and to consider the risk/benefit in patients without this sonographic predictor. Acknowledgements: To Dr. Domingo Ly Pen for his contribution to this study. Disclosure of Interest: : None declared DOI: 10.1136/annrheumdis-2014-eular.5556